Investigating the establishment of a national length standard for land surveying applications in Singapore - Tor, Yam Khoon. (2008)
The main objective was to investigate the feasibility of using precision EDM of ±(1mm + 1ppm) to establish the reference standard length of the existing Lower Pierce EDM Baseline which has no official standard length since its establishment in 1985.